Rapid prefrontal cortex activation towards aversively paired faces and enhanced contingency detection are observed in highly trait-anxious women under challenging conditions - Rehbein, Maimu Alissa; Wessing, Ida; Zwitserlood, Pienie; Steinberg, Christian; Eden, Annuschka Salima; Dobel, Christian; Junghöfer, Markus (Frontiers in Behavioral Neuroscience, 2015)
Relative to healthy controls, anxiety-disorder patients show anomalies in classical conditioning that may either result from, or provide a risk factor for, clinically relevant anxiety. Here, we investigated whether healthy participants with enhanced anxiety vulnerability show abnormalities in a challenging affective-conditioning paradigm, in which many stimulus-reinforcer associations had to be acquired with only few learning trials. Forty-seven high and low trait-anxious females underwent MultiCS conditioning, in which 52 different neutral faces (CS+) were paired with an aversive noise (US), while further 52 faces (CS-) remained unpaired. Emotional learning was assessed by evaluative (rating), behavioral (dot-probe, contingency report), and neurophysiological (magnetoencephalography) measures before, during, and after learning. High and low trait-anxious groups did not differ in evaluative ratings or response priming before or after conditioning. High trait-anxious women, however, were better than low trait-anxious women at reporting CS+/US contingencies after conditioning, and showed an enhanced prefrontal cortex activation towards CS+ in the M1 (i.e., 80 to 117 ms) and M170 time intervals (i.e., 140 to 160 ms) during acquisition. These effects in MultiCS conditioning observed in individuals with elevated trait anxiety are consistent with theories of enhanced conditionability in anxiety vulnerability. Furthermore, they point towards increased threat monitoring and detection in highly trait-anxious females, possibly mediated by alterations in visual working memory.